Gender, entrepreneurship and food security in Niger - DEDEHOUANOU, SENAKPON FIDÈLE ANGE; Abdelkrim, Araar (My University, 2020)
In many African countries, the income generated from the informal sector and the entrepreneurship is particularly important for reducing poverty. Previous studies have not found clear evidence on the relationship between self-employment by gender and food security. We argue that this may be a result of the gender inequality in resource accessibility. In this paper, we analyze the implication of household entrepreneurship on food security in Niger, where gender disparities in resource accessibility are reduced. We find that owning female-managed non-agricultural enterprises is positively related to food accessibility and food availability within female-headed households. The results draw the attention n reducing gender differences in resource accessibility in entrepreneurship for improving food security.
Keywords: entrepreneurship; food security; gender; Niger